Marketing Strategy and Its Impact on Business Performance through Strategic Agility in Small and Medium Enterprises - Setyowati, Ratna Faridah; Tabrani, Tabrani; Suwandi, Suwandi; Hanfan, Ahmad (Journal of Business and Economics Research (JBE), 2025)
Social media is currently an effective marketing tool for Micro, Small, and Medium Enterprises (MSMEs). The Emak Cantik Community consists of business actors who utilize social media for marketing. This study aims to confirm the effectiveness of the synergy between product innovation, financial literacy, and market orientation on business performance in the Emak Cantik community, both directly and indirectly through strategic agility. This study employed a descriptive method and quantitative analysis using a questionnaire distributed to 155 respondents who are members of the Emak Cantik community. The results of the LISREL analysis show that strategic agility (48%) and financial literacy (44%) have a significant effect on business performance, while product innovation (5.2%) and market orientation (0.24%) have no effect. Meanwhile, product innovation (42%), financial literacy (39%), and market orientation (51%) have a significant effect on strategic agility. The mediation test shows that strategic agility successfully mediates the influence of product innovation, financial literacy, and market orientation on business performance. The contribution of this study is to provide the latest empirical evidence on the mediation mechanism of strategic agility that can be used as a basis for developing strategies to strengthen MSMEs in the digital era.